Proceedings of the 5th International Conference on Automotive User Interfaces and Interactive Vehicular Applications 2013
DOI: 10.1145/2516540.2516578
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability, transport and design

Abstract: Private vehicle use contributes a disproportionately large amount to the degradation of the environment we inhabit. Technological advancement is of course critical to the mitigation of climate change, however alone it will not suffice; we must also see behavioural change. This paper will argue for the application of Ergonomics to the design of private vehicles, particularly lowcarbon vehicles (e.g. hybrid and electric), to encourage this behavioural change. A brief review of literature is offered concerning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…For instance, former results indicate that speed choices (e.g., variable vs. constant speed) relate to both knowledge and fuel efficiency (Franke et al, 2016a). Second, due to the complexity that HEV eco-features introduce to the drivetrain (e.g., McIlroy et al, 2013), aspects of technical system knowledge could be directly reflected on the operational level of driving (Michon, 1985), in the specific implementation of eco-driving (similar to procedural knowledge; see, e.g., Anderson, 1982;McIlroy & Stanton, 2015). If so, hypothesized differences in eco-driving behavior that depend on a driver's individual knowledge might be identified only by methods providing precise descriptions or observations of the concrete strategy implementations (e.g., assessed in interview, field, or driving simulator studies; Stanton et al, 2013; for an example, see Pampel, Jamson, Hibberd, & Barnard, 2015).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, former results indicate that speed choices (e.g., variable vs. constant speed) relate to both knowledge and fuel efficiency (Franke et al, 2016a). Second, due to the complexity that HEV eco-features introduce to the drivetrain (e.g., McIlroy et al, 2013), aspects of technical system knowledge could be directly reflected on the operational level of driving (Michon, 1985), in the specific implementation of eco-driving (similar to procedural knowledge; see, e.g., Anderson, 1982;McIlroy & Stanton, 2015). If so, hypothesized differences in eco-driving behavior that depend on a driver's individual knowledge might be identified only by methods providing precise descriptions or observations of the concrete strategy implementations (e.g., assessed in interview, field, or driving simulator studies; Stanton et al, 2013; for an example, see Pampel, Jamson, Hibberd, & Barnard, 2015).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Due to the comparatively complex energy flows in the HEV (McIlroy, Stanton, Harvey, & Robertson, 2013; e.g., bidirectional energy flow), drivers who generally use different sets of ecodriving strategies can have similar energy efficiencies (Franke, Arend, McIlroy, & Stanton, 2016a). However, specific eco-driving strategies that include the usage of eco-features (i.e., interaction patterns with eco-features) tend to be associated with increased or decreased fuel efficiency (Franke et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Second, building upon these results, an important implication is that technical system knowledge, as the more important factor regarding eco-driving success, was exclusively and strongly related to HEV Eco-Driving Knowledge acquisition by reading. A possible reason for this might be that the rather complex HEV powertrain (McIlroy et al, 2013) requires rather specific knowledge that cannot be gained in interaction with the system but only by external sources such as websites or manuals. In comparison, acquiring knowledge by interacting with the vehicle (testing and monitoring) was more related to strategy knowledge.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…For advancing knowledge on user-energy interaction, studying eco-driving in hybrid electric vehicles (HEVs) constitutes a particularly relevant field. This is due to the complexity of the HEV powertrain that is characterized by an electric motor as well as a combustion engine and the bidirectional energy flow between the wheels and the battery introduced by regenerative braking (McIlroy et al, 2013;Cocron et al, 2013). Indeed, it has been shown that technical system knowledge as well as the selection and implementation of specific eco-driving strategies are major factors for achieving optimal energy efficiency with HEVs (Arend and Franke, 2017;Franke et al, 2016).…”
Section: Introductionmentioning
confidence: 99%